Finding Maternal Histories - Vandenberg-Daves, Jodi (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
This article explores the challenges of finding maternal histories, challenges whichstem both from history’s emphasis on men and public institutions, and from broadcultural devaluation of maternal work in patriarchal societies. “Finding Maternal Histories” also illuminates the resourcefulness and creativity of researchers of maternal experiences and representations of motherhood. Drawing together themes from all the articles in this volume, this introductory piece points to themes in dominant depictions and discourses of motherhood. It also draws attention to women’s multi-faceted challenges, directly and indirectly, to problematic cultural representations and to social and economic restrictions imposed upon mothers in various times and places,in history and today.